Formação em contexto de professoras da educação infantil: um estudo de caso - Hollanda, Mônica Petralanda de (2007)
Continuous training for Childhood Education teachers constitutes one of the conditions necessary to improve the standard of educational services provided to small children. This research has sought to determine and analyse how teachers understand training schemes in a particular context. In particular, it has attempted to describe the features of a context where training occurred, with the aim of enabling a more effective analysis to be conducted of the following: their possible influence on the way this scheme was carried out; the perspectives of teachers regarding the existing relationship between training in context and other experiences of continuous training that they have undergone; and finally an identification of which aspects of the training strategies in context can make it easier or more difficult for them to achieve their objectives. As a theoretical basis, the study had the socio-constructivist perspective of Vygotsky (1994, 2000, 2004) and the ecology of human development of Bronfenbrenner (1992, 1996). Using this as a reference-point, a qualitative case study was carried out, together with the Childhood Education teachers at a public institution in Fortaleza, Ceará (Brazil), where participant observation and interviews were conducted with these professionals at different stages of the project (assessment, planning and intervention). On the whole, the teachers were aware that the purpose of the work was concerned with improving the standards of educational services being offered and from its earliest stages, regarded it as a teacher-training scheme. Their recognition of its formative character was linked to a number of strategies that were adopted by the group. At first, it was connected to the study and employment of the Child Involvement Scale; in the second stage, it was put into effect in some Childhood Education institutions of a high standard, and in the final phase it was applied to theoretical studies and activities that could be described as experimental. From the time of the initial assessment, the teachers turned their attention to work which had features that could be regarded as a central part of the training in context schemes. They were also aware of how the continuous training scheme differed from previous experiences insofar as it was continuous, prepared in partnership with the professional staff of the institution and geared towards a discussion of the needs and interests arising from everyday pedagogical practices. The factors that appear to be of crucial importance in involving the teachers in the process include the following: their gradual willingness to take part in an active way, a concern about contextualizing and understanding the weaknesses of the pedagogical work being carried out at that time, and the long period of living together. This last factor implied the need to establish affective relationships between members of the group, which could allow them to feel at ease in revealing what they did not know and learn how to cope with their inherent difficulties by undergoing a process of change. The teachers underlined the importance of having a theoretical foundation for their reflections on professional practice and referred to the way this training scheme was closely linked to the changes that they had observed in their pedagogical activities.